EVEN VERTEX ODD MEAN LABELING OF TRANSFORMED TREES - Eyanthi, P.J; Ramya, D; Selvi, M (TWMS journal of applied and engineering mathematics, 2020)
Let G = (V, E) be a graph with p vertices and q edges. A graph G is said have an even vertex odd mean labeling if there exists a function f : V(G) [right arrow] {0, 2,4,..., 2q} satisfying f is 1-1 and the induced map f* : E(G) [right arrow] {1, 3, 5,..., 2q -1} defined by f* (uv) = [f(u)+f([upsilon])/2] is a bijection. A graph that admits even vertex odd mean labeling is called an even vertex odd mean graph. In this paper, we prove that [T.sub.p]-tree (transformed tree), T@[P.sub.n], T@2[P.sub.n] and (To[K.sub.1,n]) (where T is a [T.sub.p]-tree), are even vertex odd mean graphs. Keywords: mean labeling, odd mean labeling, [T.sub.p]--tree, even vertex odd mean labeling, even vertex odd mean graph. AMS Subject Classification: 05C78